Mapping of national documentary control and metric studies that characterize national and individual identity. Stage I - Mora Valverde, María Marjorie (2010)
This is a project of the School of Library, Documentation and Information of the National University, carried out to support UNESCO's initiative to build the Memory of the World (UNESCO, 1995) and contribute to facilitate universal access to documentation. To this end, the School of Librarianship has encouraged its students to carry out final graduation papers on document control.